1996
DOI: 10.1159/000213768
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fluids in Elderly Hospital Patients with Cognitive Impairment

Abstract: Sixty patients (mean age 80 years) with cognitive impairment who required parenteral fluids for at least 48 h were randomized to receive either intravenous (i.v.) or subcutaneous (s.c.) fluids. There was no significant difference in the mean volume of fluid prescribed over 48 h in the two groups (s.c. 3.3 litres vs. i.v. 3.6 litres) or in the proportion of prescribed fluids actually administered (s.c. 0.82 vs. i.v. 0.76). After adjusting for baseline differences, there was no difference between serum urea or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
71
0
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 6 publications
3
71
0
14
Order By: Relevance
“…In contrast with Slesak et al [3], the RCT by O'Keeffe and Lavan [4] found no significant difference in the amount of fluid or the proportion of prescribed mean (standard deviation) volume administered by IV as compared to SC infusion (0.76(0.14) litres vs 0.82(0.12) litres, p = 0.1). There was also no significant difference found between serum creatinine or urea between the two groups.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast with Slesak et al [3], the RCT by O'Keeffe and Lavan [4] found no significant difference in the amount of fluid or the proportion of prescribed mean (standard deviation) volume administered by IV as compared to SC infusion (0.76(0.14) litres vs 0.82(0.12) litres, p = 0.1). There was also no significant difference found between serum creatinine or urea between the two groups.…”
Section: Resultsmentioning
confidence: 64%
“…O'Keeffe and Lavan [4] also carried out a RCT of subcutaneous fluids in elderly hospital patients in Britain. In this study the 60 participants (mean age 80 years) were cognitively impaired patients admitted to an acute geriatric unit who required parenteral fluids for at least 48 hours because of mild dehydration on poor oral intake.…”
Section: Resultsmentioning
confidence: 99%
“…Reported to be safe and well tolerated [6][7][8][9] and to deliver an equivalent fluid volume, 10 compared with intravenous hydration, for adults with mild/moderate dehydration, subcutaneous administration requires no advanced skills to start or to maintain 11,12 and may avoid certain complications of intravenous hydration. 8,13,14 Furthermore, multiple sites are appropriate for subcutaneous access, 15 and lines can be inserted quickly and maintained in relatively insensitive sites, 10,13 which makes it potentially easier, faster, and more economical than intravenous treatment. 10,11,13,15,16 Subcutaneous fluid and drug absorption can be accelerated by hyaluronidase, a spreading enzyme.…”
mentioning
confidence: 99%
“…8,13,14 Furthermore, multiple sites are appropriate for subcutaneous access, 15 and lines can be inserted quickly and maintained in relatively insensitive sites, 10,13 which makes it potentially easier, faster, and more economical than intravenous treatment. 10,11,13,15,16 Subcutaneous fluid and drug absorption can be accelerated by hyaluronidase, a spreading enzyme. [17][18][19][20][21] Hyaluronidase depolymerizes hyaluronan (a viscous component of the interstitial space that inhibits bulk fluid flow), decreasing tissue resistance to subcutaneous fluid administration.…”
mentioning
confidence: 99%
“…Isotonic fluids may be introduced into subcutaneous tissues where the aim is to correct mild to moderate dehydration in elderly patients (especially in a chronic care setting where intravenous access in the infirm and elderly is notoriously difficult), in addition to being a less invasive route of drug administration in palliative management where opioid and antiemetic treatment is frequently warranted 2. Fluid replacement by the subcutaneous route is relatively safe, easier to initiate, demands less nursing time, is more cost effective than intravenous therapy, causes less discomfort, minimises the risk of intravascular infection,3 does not immobilise a limb (since it may be given into anterior abdominal tissues), and has been found to be less distressing for patients 4. The use of hyaluronidase in the infused solution augments the rate of fluid uptake and volumes up to 3000 ml can be delivered over 24 hours 5…”
mentioning
confidence: 99%